Attitudes and perceived barriers in geriatric dental care among undergraduate dental students in capital region of Andhra Pradesh - Talluri Devaki; Krishna Priya Mallikapuram; Bommireddy Vikram Simha; Viswa Chaitanya Chandu; Nijampatnam P M Pavani; Ravoori Srinivas (Wolters Kluwer Medknow Publications, 2020)
Background: This is the era of the elderly. In India, there is an exponential increase in the aging population. Increase in longevity means that the community will have to bear a greater burden of disease. The general health and well-being of older adults are related to their oral health. Aim: The to study the perceived barriers and attitudes of undergraduate dental students towards geriatric dental care. Materials and Methods: Four hundred and eighty senior dental students participated in the present cross-sectional questionnaire study. The first sought background information including gender, age, prior treating in geriatric dental care, and prior experience in treating the elderly in their education. The responses were categorized in a Likert scale. Data were analyzed using SPSS version 20. P < 0.05 was considered as statistically significant. Fisher exact test was used to know the attitude to work with elderly and the barriers in elderly dental care. Gender-wise comparison of mean attitude score toward the elderly was done. Results: The perceived barriers of dental students' showed significant association with respect to financial ability of the elderly (P = 0.017), follow-up of elderly patients (P = 0.04), elderly patient compliance (P = 0.05), and inadequate communication skills in treating elderly patients (P = 0.05). Females (2.500 ± 0.48) showed positive attitude when compared to male (1.166 ± 0.19) study subjects. The total attitudes mean score was 1.87 ± 0.34. Conclusions: Even though dental students were willing for elderly dental care, student's inadequate knowledge of geriatric care, poor communication skills, and lack of confidence in management of elderly patients are the identified barriers.